2008
DOI: 10.1007/s10562-008-9799-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement in Activity and Stability of Pt/TiO2 Catalyst for Water Gas Shift Reaction Via Controlling the Amount of Na Addition

Abstract: Na promoted Pt/TiO 2 catalysts have been studied under high severity, near equilibrium, conditions for use as a single stage WGS catalyst. Addition of 3 wt% Na to a 1 wt% Pt/TiO 2 catalyst has been found to improve water gas shift activity significantly compared to Pt/TiO 2 , Pt/CeO 2 , and Pt-Re/TiO 2 catalysts. This catalyst is stable when the reaction temperature is higher than 250°C. Deactivation occurred when the reaction temperature was lower than 250°C, however, returning the temperature to higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 22 publications
1
18
0
1
Order By: Relevance
“…This phenomenon allows water adsorption followed by its dissociation and the creation of hydroxyl groups. However, the problem remains whether at room temperature these hydroxyl groups can react with carbon monoxide [reaction (9)]. To check it, the following test was conducted.…”
Section: The Activity Tests and Overall Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon allows water adsorption followed by its dissociation and the creation of hydroxyl groups. However, the problem remains whether at room temperature these hydroxyl groups can react with carbon monoxide [reaction (9)]. To check it, the following test was conducted.…”
Section: The Activity Tests and Overall Discussionmentioning
confidence: 99%
“…The catalytic oxidation of CO has been studied on numerous both metallic and oxide catalysts over the years [1][2][3][4][5][6][7]. The mixture of copper and manganese oxides (hopcalite) or gold deposited on some metal oxides exhibits very high activity towards the lowtemperature oxidation of CO [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process can successfully reduce CO levels to less than 1% in a large scale H 2 plant [4]. However, the conventional WGS unit is not suitable for a compact reformer due to restrictions in volume, weight and cost [5]. Thus, it is necessary to develop advanced catalysts for single stage WGS, which can do HTS and LTS at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…However, these catalyst systems suffer from certain drawbacks when used in small-scale fuel processors with characteristics such as cyclic operation and the possibility of air contamination [3,4]. To overcome these weak points of commercial WGS catalysts, some noble metal catalysts including Pt group metals have been extensively studied [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Panagiotopoulou and Kondarides [5] compared the WGS activity among various noble metal catalysts supported on Al 2 O 3 and reported that the catalytic activity followed the order of Pt>Rh≈Ru>Pd.…”
Section: Introductionmentioning
confidence: 99%